Developing an Indicator System for Monitoring, Analyzing, and Assessing Airport Sustainability - Janic, Milan (European Journal of Transport and Infrastructure Research, 2010)
This paper deals with developing an indicator system for monitoring, analyzing, and assessing sustainability of airports. The sustainability implies simultaneous increasing of the overall socialeconomic benefits and increasing at a slower rate, stagnating, and/or diminishing of the negative impacts of these airports during the specified medium- to long-term period of time. The indicator system consists of the indicators and their measures reflecting the airport operational, economic, social, and environmental dimension of performances. These include effects-benefits and impacts-externalities of the airport operations. The effects-benefits include mainly the airport contribution to local employment, regional (local) economy, and consequently GDP (Gross Domestic Product). The impacts-externalities embrace local noise, air pollution, congestion and delays, land use (take), and waste. The particular indicators and their measures are specified respecting interests and attitudes of particular actors involved such as users and providers of air transport services, private and public investors, governmental organizations, local community members, lobbies and pressure groups, and general public. An application of the proposed indicator system has shown that it could be considered as an initial step in developing a “tool” for assessing the current and prospective level of the airport sustainable development.